Autorzy:Jerzy Janowicz
Wydawnictwo:Nowa Era
Rok wydania:2016
Oblicz średnią arytmetyczną liczb 4.6 gwiazdek na podstawie 5 opinii

`a)\ (2^3+2^4+2^5+2^6)/4=(2^3*1+2^3*2+2^3*2^2+2^3*2^3)/(2^2)=(2^3*(1+2+2^2+2^3))/2^2=` 

`\ \ \ =2^(3-2)*(1+2+4+8)=2*15=30` 

 

 

`b)\ (3^3+3^4+3^5)/3=(3^3*1+3^3*3+3^3*3^2)/3=(3^3*(1+3+3^2))/3=` 

`\ \ \ =3^(3-1)*(1+3+9)=3^2*13=9*13=117` 

 

 

`c)\ (4^-1+4^-2+4^-3+4^-4)/4=4^-1/4+4^-2/4+4^-3/4+4^-4/4=` 

`\ \ \ =4^-2+4^-3+4^-4+4^-5=1/4^2+1/4^3+1/4^4+1/4^5=` 

`\ \ \ =1/16+1/64+1/256+1/1024=64/1024+16/1024+4/1024+1/1024=85/1024` 

 

 

`d)\ ((-5)^1+(-5)^2+(-5)^3+(-5)^4)/4=(1/5+1/5^2+1/5^3+1/5^4)/4=`      

`\ \ \ =(1/5+1/25+1/125+1/625):4=(125/625+25/625+5/625+1/625)*1/4=`       

` \ \ \ =156/625*1/4=39/625`  

` `